Challenges in estimating the severity of kidney dysfunction in critically ill children - Ramachandran Rameshkumar; Muthu Chidambaram; Rohit Bhowmick (Wolters Kluwer Medknow Publications, 2024)
Acute kidney injury (AKI) is a common problem in critical care settings and conferred an increased risk of morbidities and mortality. The pendulum has shifted to the increasing number of children with comorbidities exposed to potential kidney damage. AKI is a complex clinical syndrome due to heterogeneous etiology. There has been an evolution in the definition and staging of AKI over the past two decades. However, estimating glomerular filtration rate in rapidly changing kidney function remains challenging. Although biomarkers are promising in AKI identification, timing is crucial in deciding which biomarker to measure. The outcome of AKI is not always recovery, but it is an interconnected syndrome with acute and chronic kidney disease.